“KLASE” FOR MC: THE TEACHING-LEARNING PROCESS IN THE PUBLIC SCHOOL SPED CENTERS IN CEBU, PHILIPPINES - Patac, Arlene Balio (PEOPLE: International Journal of Social Sciences, 2015)
For a student, the classroom is an important aspect of learning for it is where most of their learning takes place. The classroom for special children—the mentally challenged—is equally important to look into as to a general education classroom. This study explores the teaching-learning process that takes place in the classroom or “klase” for mentally challenged children of three public school sped centers in Cebu, Philippines: the organization of the classroom, the classroom management, teaching strategies, and problems encountered by the SPED teachers. This is anchored on the dimensions of classroom organization and classroom management theories of B.F. Skinner and Jacob Kounin. Employing the qualitative-descriptive research method through video documentations, it shows that teaching-learning process takes place in the class or “klase” for mentally challenged in the three sped centers, thus revealing the commonalities and differences in the classroom organization. Classroom management includes rules and procedures that need to be followed by the children, and also takes into account positive reinforcement, reward style, and punishment used by the SPED teachers. Teaching strategies embrace motivations, use of Individual Instruction Plan or IIP for each child and the utilization of an eclectic teaching strategy. Problems encountered in teaching these mentally challenged students involve short time period considering the number of pupils handled, nature of disabilities, tantrums and financial status of these children. This brought to light that classroom organization and classroom management pose a great impact on the learning of these mentally challenged students